A planificação da atenção à saúde na efetivação do eixo transversal do PMAQ - Cruz, Kamilla Borges (2021)
The Programa de Melhoria do Acesso e da Qualidade da Atenção Básica (Program for Improving Access and Quality of Primary Care - PMAQ) was established in 2011 and has as its transversal axis a set of actions developed by management and workers to generate changes and seeking better access and better quality of Primary Care. These actions are organized into five dimensions: self-assessment, monitoring, continuing education, institutional support, and horizontal cooperation. The Conselho Nacional de Secretários de Saúde (National Council of Health Secretaries - CONASS) promoted the pilot project of Primary Care Planning in Santa Maria, whose proposal aimed at strengthening Primary Care and articulating the Health Care Network. This study aimed to evaluate the effects of Primary Health Care Planning for the realization of PMAQ Transversal Axis. This is qualitative evaluative research, held in 2020 in Santa Maria, the host city of the pilot project for Primary Care Planning in Rio Grande do Sul. Eleven workers took part in the survey who completed face-to-face hours in Planning above 75% and were linked to PMAQ teams in the second and third cycles. The research was approved by the Research Ethics Committee of the Federal University of Santa Maria. Data were analyzed based on Minayo's operative proposal. The analysis allowed us to identify that the Planning promoted self-evaluation processes by the workers. However, the objectives, as well as the planning to overcome the difficulties, were carried out vertically, going against the recommendations of PMAQ. Monitoring was identified in the encouragement of registration and there was instrumentalization for data analysis, based on epidemiological panels and Coelho's scale. Continuing Education enabled the resumption of concepts and instigated reflective processes, triggering later reflective moments, which were developed by the management and by the workers themselves. Municipal and state managers, tutors and CONASS were identified as institutional supporters. The role of this supporter got by the data was to present answers to the difficulties encountered, to suggest alternatives, by valuing the professional outside the unit as the holder of knowledge, diverging from what PMAQ suggested of a rupture of the verticalized model, by enabling solidary relationships. Participants revealed that Horizontal Cooperation was based on instinctive and individual relationships, according to affinity, but they consider that the Planning was a moment of rapprochement and recognition of peers, which strengthened relations and allowed to expand cooperation, without the management having realized the encouragement of this exchange. Planning brought points of convergence with the transverse axis of PMAQ, but tangentially. We understand that PMAQ should be transversal to all themes, validating this ministerial strategy, in the search for continuous progress to strengthen Primary Care as an orderer of the Health Care Networks. It also brought secondary gains, such as the approximation between workers. It fostered discussion processes between management, workers and educational institutions and generated important unrest.